Material-Based Learning in Architecture Design Studio: From ‘Beaux-Arts’ to ‘Bauhaus’ into Current Educational Era - Resza Riskiyanto (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2023)
This paper presents the development of ways of learning based on material and materiality in architectural education. Some basic principles were founded in a material-based studio learning process when previously developed by Ecole des Beaux-Arts and Bauhaus, two architecture schools established along with the rise of new materials and technology introduced in the industrialization era. Since both schools implemented material thinking as part of their learning process, it has undergone a transformation following the development of new technologies. But there may still be some principles that exert a strong influence on some schools around the world. The critical question is what makes material-based learning still important to develop in architecture education?The qualitative research in this article was conducted in a third-year architectural design studio that applies material-based design through a case study of two different types of materials. This study aims to see the relevance of material-based learning principles that were previously applied to the current methods and practices of architectural education. The analysis is carried out by investigating the development of the learning method in accordance with material issues that are resolved with a different approach. The results of this study indicate that the understanding of materiality is a fundamental thing that needs to be maintained in architecture education to develop critical thinking through material-based learning.